Observaciones sobre la relación entre la “cosmo-lógica” y la construcción de la persona en el espiritismo cubano - Diana Espirito Santo (Ateliers d'Anthropologie)
Speaking of syntheses or mixtures of religious traditions without taking into account the ontologies that operate in them leads to certain mistakes. In this paper I suggest that popular forms of Cuban spiritism (espiritismo) offer a genuine “anthropology” or indigenous theory of personhood that acts as a dynamic driving force towards, and for, its sister Afro-Cuban religions, diversifying personal practices through the demands of the dead with whom the mediums communicate. From this point of view, the practice of mediumship could be described as an ontogenetic engine, creating, in each person, the possibility of existential self-recognition through self-production. I argue that spiritist practices therefore constitute an enlightening window onto the dynamic relationship between the internal and external aspects of Cuban religious syncretism in general. One further objective of this article is to demonstrate that in addition to the need to understand syncretism as something mutable, and in constant metamorphosis, it is also necessary to articulate the principal concepts through which the nuances of these flows manifest themselves. The notion of ‘cosmo-logic’ is proposed in order to elucidate these nuances.